Discovery of a novel oxadiazine derivative of glucocorticoids endowed with DNA binding activities and molecular docking studies - Sultanat; Ali, Abad; Asif, Mohd; Rizvi, Asim; Farhan, Mohd; Zaman, Shamsuz (Journal of Taibah University for Science, 2019)
A series of new glucocorticoid oxadiazines (4-6) were synthesized by reacting glucocorticoids (1-3) with thiosemicarbazide and its derivatives. The structural assignment of products is confirmed on the basis of IR, H-1 NMR, C-13 NMR, MS and analytical data. The synthesized compounds (4-6) obeyed the Lipinski's "Rule of Five" analysis based on a computational prediction of molecular and pharmacokinetic properties. The interaction studies of compounds (4-6) with DNA were carried out by employing single-cell gel electrophoresis (comet assay), UV-vis and fluorescence spectroscopy. Compounds (4-6) were found capable of cellular DNA degradation breakage in isolated normal human lymphocytes. Viscometric and steady-state measurements further correlated with the comet assay studies. Hence, it could be suggested that the glucocorticoid compounds bearing a core oxadiazine scaffold would be a potent biological agent. Molecular docking studies further characterize the interaction of the synthesized compounds with DNA.